Heart-rate changes on standing in elderly patients with orthostatic hypotension. - White, N (1980)
1. The heart-rate changes on standing were studied in 16 elderly patients with idiopathic orthostatic hypotension and compared with those of 20 controls. The mean age of both groups was 78 years, and all were in sinus rhythm. 2. The patients with orthostatic hypotension differed from the control patients in having no early peak in heart rate, and a significantly smaller and slower rise in heart rate within the first 40 s after standing (P less than 0.05). 3. It is concluded that there is a failure of the autonomic reflex in elderly patients with orthostatic hypotension, which may contribute towards their symptoms.